Are Obesity Levels Increasing in the “Transition Countries?” - palevskaya, Svetlana (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, obesity and overweight has been recognized as a rising public issue in all countries in the world, especially among Middle-Eastern countries. From 1980 when the prevalence of obesity more than doubled, individual studies have been published. However, no evidence is collated on the overall problem in Middle East. Objective: to systematically review the prevalence of obesity/overweight in Middle East region. Methods: a systematic review of studies, which measured prevalence of obesity/overweight in countries of Middle East. Results were given separately for women/men and urban/rural participants. Results: In this review, ten studies were selected and included. All studies were conducted in Middle East countries in different time periods. Final analysis showed that overall, prevalence of obesity and overweight are increasing trend in this region. In addition, it was demonstrated that females are more overweight and obese. 31-59 age groups had the highest prevalence of obesity/overweight among both sexes. Urban participants are more obese and overweight than rural. Conclusion: Prevalence of obesity and overweight has increasing trend in Middle East Region. That is why; governments of this region should develop special programs and actions, which will consider specific cultural and social barriers of Middle East.